Mg ALLOY AND METHOD FOR MANUFACTURING Mg ALLOY

By reducing the Sc content in Mg-Sc alloys and adding specific additive elements to stabilize the BCC phase, the Mg alloy achieves improved ductility and strength, addressing supply chain and cost issues while enhancing mechanical properties.

JP2025060134APending Publication Date: 2025-04-10TERUMO KK +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023170674
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10

AI Technical Summary

Technical Problem

Mg-Sc alloys require a relatively large amount of Sc, which is a rare and unstable supply, limiting their commercialization due to high costs and supply chain issues.

Method used

An Mg alloy with a reduced Sc content is developed by adding a specific proportion of Sc along with other additive elements like Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd, stabilizing the BCC phase and achieving transformation-induced plasticity.

Benefits of technology

The Mg alloy achieves both high ductility and strength while reducing the Sc content, thereby addressing supply chain stability and cost issues, and enhancing mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060134000011
    Figure 2025060134000011
  • Figure 2025060134000012
    Figure 2025060134000012
  • Figure 2025060134000013
    Figure 2025060134000013
Patent Text Reader

Abstract

To provide a Mg alloy with less content of Sc, in which both ductility and hardness are satisfied.SOLUTION: An Mg alloy is an alloy having Mg as a main component, containing Sc within the range of more than 10 at.% and 25 at.% or less, containing a first additive element which consists of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd and Gd by 0.01 at.% or more and 9 at.% or less, with the balance being Mg and inevitable impurities, having a BCC phase, and exhibiting transformation-induced plasticity under an environment of 0°C to 50°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an Mg alloy with transformation induced plasticity and a method for producing the Mg alloy. [Background technology]

[0002] Magnesium alloys (hereinafter, Mg alloys) are low-density, lightweight, and have a high specific strength, and are also abundant in resources. For these reasons, they are expected to be used in a variety of fields, including as structural materials for automobiles and aircraft, and as medical materials. However, Mg alloys have not yet been fully put to practical use. This is due to insufficient mechanical properties, such as poor ductility, low strength, and poor workability.

[0003] One of the reasons why ordinary magnesium alloys have poor ductility and strength is that the main phase has an HCP (hexagonal close-packed) structure, and it has been pointed out that early fracture occurs due to localized large deformation inside the double twins formed during deformation. As a solution to this problem, attempts have been made to control the crystals, such as by refining or randomizing the crystal grains (Non-Patent Document 1), but the structure remains HCP, and there is anisotropy due to the structure, so there is a limit to how much ductility can be improved.

[0004] In addition, there is a Mg-Li alloy as a technology for improving the workability of Mg alloys (Patent Documents 1 and 2). When a certain amount of Li is added to Mg, the crystal structure changes from HCP to BCC (body-centered cubic) structure, improving the workability. However, as the lithium content increases, the corrosion resistance decreases, and furthermore, the Mg-Li alloy has problems such as low hardness and strength, and poor thermal stability.

[0005] As an Mg alloy to solve the above problems, Mg-Sc alloys, which are Mg alloys with a certain amount of Sc added, have been developed. It has been reported that the strength of Mg alloys is improved by adding a certain amount of scandium (Sc) to Mg (Non-Patent Document 2). It has also been reported that Mg-Sc alloys undergo transformation induced plasticity (TRIP) deformation, which gives them both high ductility and strength (Non-Patent Document 3).

[0006] According to these reports, Mg-Sc alloys containing a certain amount of Sc can be said to be alloys that combine good ductility and strength, and are expected to be used in a variety of industrial fields. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2011-58089 A [Patent Document 2] JP 2001-40445 A [Non-patent literature]

[0008] [Non-Patent Document 1] Miura, H. et al.,2010, Trans. Nonferrous Met. Soc. China, Vol. 20, p.1294-1298. [Non-Patent Document 2] CJ Silva et al., Mater. Sci. Eng. A, vol 692 (2017) pp 199-213 [Non-Patent Document 3] Keisuke Yamagishi. et al., Journal of Alloys and Compounds 931 (2023) 167507 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the inventors have noticed that the above-mentioned Mg-Sc alloy must contain a relatively large amount of Sc. Sc, a rare metal, is produced in only a limited number of countries, and its production volume is also small worldwide, which means that there is a problem of unstable supply. Therefore, there is a possibility that the supply of the Mg-Sc alloy itself, which contains a relatively large amount of Sc, will also become unstable.

[0010] The present invention has been made to solve the above problems, and has an object to provide a Mg alloy that has both ductility and strength while reducing the Sc content. [Means for solving the problem]

[0011] The present inventors have conducted extensive research to solve the above problems, and as a result have found that the above problems can be solved by an Mg alloy that contains, in addition to Mg and Sc, a specified additive element in a specified ratio, has a BCC phase, and further has transformation induced plasticity, thereby completing the present invention.

[0012] That is, the above objects can be achieved by the present invention having the following configuration, and the present invention includes the following aspects and configurations.

[0013] One aspect of the present invention is 1. An alloy mainly composed of Mg, Contains Sc in the range of more than 10 at.% and not more than 25 at.%, Contains 0.01 at.% or more and 9 at.% or less of a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd; The balance is Mg and inevitable impurities. It has a BCC phase. This is a Mg alloy that exhibits transformation induced plasticity in an environment of 0℃ to 50℃.

[0014] 2. In the Mg alloy described in 1 above, it is preferable that the volume fraction of the BCC phase decreases when a strain of 10% or more is applied.

[0015] 3. In the Mg alloy described in 1. or 2. above, it is preferable that the fracture elongation is 20% or more and the yield stress is 150 MPa or more and 1000 MPa or less.

[0016] 4. In the Mg alloy according to any one of 1. to 3. above, the Sc equivalent (Sc eq ) preferably satisfies the following formula (1).

[0017]

number

[0018] 5. In the Mg alloy described in any one of 1. to 4. above, it is preferable that the Mg alloy further contains at least one selected from the group consisting of Ca, Mn, Zr, and Ce as a second additive element, the content of the second additive element is 0.01 at.% or more and 2.0 at.% or less, and the sum of the content of the first additive element and the content of the second additive element is 9 at.% or less.

[0019] 6. In the Mg alloy according to any one of 1. to 5. above, the volume fraction of the BCC phase may be less than 90 volume %.

[0020] One aspect of the present invention is 7. A method for producing a magnesium alloy having a BCC phase and transformation induced plasticity, comprising the steps of: a melting step of melting each component so that the alloy contains Mg as a main component, Sc in a range of more than 10 at.% and not more than 25 at.%, a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at.% or more and not more than 9 at.%, and the balance consisting of Mg and unavoidable impurities; A solution treatment process in which the alloy is solutionized at a temperature of 500°C or higher; and a cooling treatment step of cooling at a cooling rate of 1000°C / min or faster.

[0021] 8. In the manufacturing method of the Mg alloy described in 7 above, it is preferable that in the melting step, the alloy further contains at least one element selected from the group consisting of Ca, Mn, Zr, and Ce as a second additive element, the content of the second additive element is 0.01 at.% or more and 2.0 at.% or less, and the sum of the content of the first additive element and the content of the second additive element is 9 at.% or less.

[0022] 9. In the method for producing an Mg alloy as described in 7. or 8. above, it is preferable that the volume fraction of the BCC phase is less than 90 volume %.

[0023] 10. The method for producing an Mg alloy according to any one of the above items 7. to 9. preferably further comprises an aging treatment step in which aging treatment is performed in a temperature range of 50°C to 400°C. Effect of the Invention

[0024] According to the present invention, in an Mg alloy, it is possible to reduce the Sc content while achieving both ductility and strength. [Brief description of the drawings]

[0025] [Figure 1] FIG. 1 shows the optical microscope structure of a Mg-18.7 at.% Sc (hereinafter, at.% is omitted) sample after heat treatment at each temperature. [Diagram 2]FIG. 2 shows the optical micrographs of the Mg-19.1Sc-0.5Zn sample after heat treatment at each temperature. [Diagram 3] FIG. 3 shows the optical micrographs of the Mg-17.5Sc-0.5Y sample after heat treatment at each temperature. [Figure 4] FIG. 4 shows the optical micrographs of the Mg-18.0Sc-0.5Nd sample after heat treatment at each temperature. [Diagram 5] FIG. 5 shows the optical micrographs of the Mg-17.3Sc-1.0Gd sample after heat treatment at each temperature. [Figure 6] FIG. 6 shows the optical micrographs of the Mg-Sc-Gd samples after heat treatment at various temperatures. [Figure 7] FIG. 7 shows the stress-strain curve of the Mg-18.9Sc-0.5Zn (Example 1) test piece. [Figure 8] FIG. 8 shows the stress-strain curve of the test piece of Mg-13.9Sc-2.9Y (Example 7). [Figure 9] FIG. 9 shows the stress-strain curve of the test piece of Mg-18.4Sc-1.0Nd (Example 8). [Figure 10] FIG. 10 shows the stress-strain curve of the Mg-17.9Sc-1.0Gd (Example 12) specimen. [Figure 11] FIG. 11 shows the appearance of the test pieces of Examples 1, 3, 6, 7, 11 and 12 after fracture. [Figure 12] FIG. 12 shows the results of XRD analysis of the vicinity of the fractured portion of the test pieces of Examples 1 to 4 after fracture. [Figure 13] FIG. 13 shows the results of XRD analysis of the vicinity of the fractured portion of the test pieces of Examples 5 to 7 after fracture. [Figure 14] FIG. 14 shows the results of an XRD analysis of the vicinity of the fractured portion of the test piece of Example 8 after fracture. [Figure 15] FIG. 15 shows the results of XRD analysis of the vicinity of the fractured portion of the test pieces of Examples 9 to 12 after fracture. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0026] The present invention is an alloy mainly composed of Mg, containing Sc in the range of more than 10 at.% and not more than 25 at.%, a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at.% or more and not more than 9 at.% or less, with the balance consisting of Mg and unavoidable impurities, having a BCC phase, and having transformation induced plasticity in an environment of 0° C. to 50° C. The Mg alloy according to one embodiment of the present invention having this configuration can achieve both ductility and strength while reducing the Sc content.

[0027] Hereinafter, an embodiment of the present invention will be described. Note that the present invention is not limited to only the following embodiment. In addition, in this specification, unless otherwise specified, operations and measurements of physical properties are performed under the conditions of room temperature (20°C to 25°C) and relative humidity of 40% RH to 50% RH.

[0028] [Mg alloy] The Mg alloy according to one embodiment of the present invention is an alloy mainly composed of Mg, containing Sc in the range of more than 10 at.% and not more than 25 at.%, and further containing a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at.% or more and not more than 9 at.%. The balance is made of Mg and inevitable impurities, has a BCC phase, and has transformation induced plasticity in an environment of 0°C to 50°C. The elemental composition of the Mg alloy according to this embodiment can be controlled by adjusting the amount of each element in the raw material when producing the alloy so as to obtain the above elemental composition or the elemental composition shown below.

[0029] The Mg alloy according to one embodiment of the present invention having the above-mentioned configuration can achieve both ductility and strength while reducing the Sc content. Although the details of the reason are unclear, it is believed to be due to the following mechanism.

[0030] It has been known that an Mg-Sc alloy consisting of Mg and Sc exhibits transformation induced plasticity (hereinafter also referred to as TRIP), and thus has good ductility and strength.

[0031] Here, transformation induced plasticity (hereinafter also referred to as TRIP) means that when an austenite phase (hereinafter also referred to as BCC phase or β phase) is subjected to an external force that generates strain, a martensitic transformation occurs and changes to a martensite phase (hereinafter also referred to as HCP phase or α phase). For example, when a tensile test is performed, local deformation (necking) occurs when a general alloy is deformed, and the load is concentrated at the necked part, resulting in fracture and destruction. On the other hand, in an alloy that exhibits TRIP, the BCC phase changes to the HCP phase due to the strain generated at the necked part. Since the HCP phase is stronger than the BCC phase, the strength of the necked part where the change occurs increases. As a result, the deformation of the necked part is suppressed, and further necked parts are generated in other parts of the alloy. It is believed that this leads to high strength and high ductility in an alloy that exhibits TRIP.

[0032] One of the factors that allows conventional Mg-Sc alloys to exhibit TRIP is that a certain amount of Sc stabilizes the BCC phase. As mentioned above, the BCC phase has a relatively unstable structure compared to the HCP phase, so it is thought that the BCC phase needs to be stabilized in order for TRIP to occur.

[0033] On the other hand, in the Mg alloy according to the present invention, the Sc content is reduced compared to conventional Mg-Sc alloys, and instead, a predetermined amount of a first additive element is added. By reducing the Sc content, there is a concern that the stability of the BCC phase is impaired and the occurrence of TRIP is impaired. However, in the Mg alloy according to the present invention, by further including a predetermined amount of the first additive element, the first additive element complements the role of Sc and stabilizes the BCC phase, so that TRIP is sufficiently expressed and further high strength and high ductility are achieved.

[0034] It should be noted that the above mechanism is based on speculation, and the present invention is not limited to the above mechanism in any way.

[0035] <Mg content> The Mg alloy according to one embodiment is an alloy containing Mg as a main component. The main component means that the component having the highest content (at.% (also called atomic %)) in the Mg alloy.

[0036] Here, the Mg content in the Mg alloy is preferably 60 at.% or more, more preferably 65 at.% or more, even more preferably 70 at.% or more, particularly preferably 75 at.% or more, and most preferably 80 at.% or more. The Mg content in the Mg alloy is preferably 90 at.% or less, more preferably 89.99 at.% or less, even more preferably 85 at.% or less, particularly preferably 84 at.% or less, and most preferably 83.5 at.% or less. By having the Mg content in the Mg alloy within the above range, it is possible to improve ductility and strength while ensuring the properties of magnesium such as low density and light weight.

[0037] The Mg content in the Mg alloy can be determined by analyzing the Mg alloy with an electron probe microanalyzer (EPMA). Specifically, it can be calculated by the method described in "(I) Composition analysis" in the Examples.

[0038] <Sc content> The Mg alloy according to one embodiment contains Sc in the range of more than 10 at.% and not more than 25 at.%. However, the lower limit of the Sc content (at.%) in the Mg alloy is preferably 11 at.% or more, more preferably 12 at.% or more, even more preferably 13 at.% or more, and particularly preferably 13.5 at.% or more, based on the total amount of the Mg alloy. The upper limit of the Sc content (at.%) in the Mg alloy is preferably 24 at.% or less, more preferably 23 at.% or less, even more preferably 21 at.% or less, particularly preferably 20 at.% or less, and most preferably 19.5 at.% or less, based on the total amount of the Mg alloy. Although the above range of the Sc content is smaller than that of the conventional technology, the Mg alloy according to one embodiment of the present invention can maintain good ductility and strength by being within the above range.

[0039] The Sc content in the Mg alloy can be determined by analyzing the Mg alloy with an electron probe microanalyzer (EPMA). Specifically, it can be calculated by the method described in "(I) Composition analysis" in the Examples.

[0040] <First additive element> The first additive element in the Mg alloy according to one embodiment is at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd. The first additive element is preferably at least one selected from the group consisting of Zn, Y, Nd, and Gd, and more preferably at least one selected from the group consisting of Nd and Gd. By including the first additive element selected from the above group in the Mg alloy, the ductility and strength of the Mg alloy can be further improved.

[0041] The content of the first additive element in the Mg alloy is 0.01 at.% or more and 9 at.% or less with respect to the total amount of the Mg alloy. However, the lower limit of the content of the first additive element in the Mg alloy is preferably 0.05 at.% or more with respect to the total amount of the Mg alloy, more preferably 0.1 at.% or more, even more preferably 0.2 at.% or more, particularly preferably 0.25 at.% or more, and most preferably 0.5 at.% or more. The upper limit of the content of the first additive element in the Mg alloy is preferably 7 at.% or less with respect to the total amount of the Mg alloy, more preferably 5 at.% or less, even more preferably 3 at.% or less, particularly preferably 2.5 at.% or less, and most preferably 2 at.% or less. By having the content of the first additive element in the Mg alloy within the above range, it is possible to obtain an Mg alloy that more effectively achieves both ductility and strength while reducing the Sc content.

[0042] The composition of the Mg alloy and the content of the first additive element can be determined by analyzing the Mg alloy with an electron probe microanalyzer (EPMA). Specifically, they can be calculated by the method described in "(I) Composition analysis" in the Examples.

[0043] <Temperature at which transformation induced plasticity occurs> The Mg alloy according to one embodiment of the present invention has transformation induced plasticity in the temperature range of 0° C. to 50° C., and the temperature range is preferably 5° C. to 45° C., more preferably 10° C. to 40° C., even more preferably 15° C. to 40° C., and particularly preferably 20° C. to 40° C. Since the Mg alloy has transformation induced plasticity in the above temperature range, the Mg alloy can be suitably used as a material for medical devices, for example.

[0044] <BCC phase> Although the Mg alloy according to one embodiment of the present invention has a BCC phase, the volume fraction of the BCC phase in the entire Mg alloy may be 100% by volume. That is, the Mg alloy may be composed of a single BCC phase. When the Mg alloy is composed of a single BCC phase, TRIP is easily manifested and the Mg alloy may have sufficient ductility and strength.

[0045] The volume fraction of the BCC phase in the entire Mg alloy may be less than 90% by volume. The lower limit of the volume fraction of the BCC phase in the entire Mg alloy is not particularly limited, but may be 50% by volume or more, 60% by volume or more, 70% by volume or more, or 80% by volume or more. When the volume fraction of the BCC phase is in the above range, TRIP is easily manifested in the Mg alloy, and ductility and strength can be obtained more effectively. The volume fraction of the BCC phase can be obtained by measuring the surface of the Mg alloy by X-ray diffraction (XRD) and calculating the proportion of each phase. Specifically, the method described in "(IV) Investigation of Constituent Phases" in the Examples can be adopted.

[0046] In addition, in the Mg alloy according to one embodiment of the present invention, it is preferable that the volume fraction of the BCC phase is reduced when a strain of 10% or more is applied. This configuration makes it easier for TRIP to occur in the Mg alloy, and can more effectively improve ductility and strength. Here, the reduction in the volume fraction of the BCC phase can be confirmed by measuring the surface of the Mg alloy by XRD before and after applying a strain of 10% or more and comparing the results.

[0047] Moreover, the Mg alloy according to one embodiment of the present invention preferably has a fracture elongation (El, fracture strain) of 20% or more and a yield strength (YS, yield strength) of 150 MPa or more and 1000 MPa or less.

[0048] The breaking elongation is preferably 20% or more, more preferably 25% or more, even more preferably 30% or more, even more preferably 35% or more, particularly preferably 40% or more, and most preferably 45% or more. There is no particular upper limit to the breaking elongation, but it is preferably 300% or less, more preferably 200% or less, even more preferably 150% or less, and particularly preferably 100% or less.

[0049] The yield stress is preferably 150 MPa or more and 1000 MPa or less, but may be 200 MPa or more and 900 MPa or less, 200 MPa or more and 800 MPa or less, 200 MPa or more and 700 MPa or less, 200 MPa or more and 600 MPa or less, 250 MPa or more and 900 MPa or less, 250 MPa or more and 800 MPa or less, 250 MPa or more and 700 MPa or less, or 250 MPa or more and 600 MPa or less. The fracture elongation and yield stress of the Mg alloy are in the above range, so that the ductility and strength of the Mg alloy become more sufficient, and the convenience as an Mg alloy is improved. Here, the fracture elongation and yield strength can be calculated by the method described in the examples.

[0050] 〈Sc equivalent (Sc eq )〉 The Mg alloy according to one embodiment of the present invention has a component with a predetermined Sc equivalent (Sc eq ) is preferably satisfied. Here, the Sc equivalent (Sc eq ) preferably satisfies the following formula (1).

[0051]

number

[0052] Sc equivalent in Mg alloys (Sc eq ) satisfies the above formula (1), the Mg alloy is more likely to exhibit TRIP, and it is possible to obtain a Mg alloy with improved ductility and strength. Note that the above formula (1) is derived by the method shown in the section "Calculation of single-phasing temperature and Sc equivalent" below.

[0053] Here, as mentioned above, the Sc equivalent (Sc eq ) is 19.0 <Sc eq <21.0 (in at.%), but Sc eq The lower limit of the value of Sc may be 19.1 at.% or more, 19.2 at.% or more, 19.3 at.% or more, 19.4 at.% or more, or 19.5 at.% or more. eq The upper limit of the value of may be 20.9 at.% or less, 20.8 at.% or less, 20.7 at.% or less, 20.6 at.% or less, or 20.5 at.% or less. eq ) in the above range allows the Mg alloy to fully exhibit TRIP. β is 600 <T β <700(℃), but 610 <T β <690(℃), 620 <T β <680(℃), 630 <T β <670(℃) may be acceptable.

[0054] <Calculation of single-phase temperature and Sc equivalent> In order to evaluate the effect of each added element on the stability of the β phase, the β single-phase temperature (T β ) change (ΔT β ) and ΔT β The Sc equivalent was calculated by comparing the sign and magnitude of with Sc.

[0055] First, T βThe method of determining T was based on optical microscope observation and was as follows. If the sample had an equiaxed α phase, it was determined to have α + β two-phase, and if not, it was determined to have a β single-phase. The midpoint between the highest temperature at which a two-phase structure was obtained and the lowest temperature at which a single-phase structure was obtained was determined as T. β For example, Fig. 1 shows the optical micrographs of a Mg-18.7 at.% Sc (hereafter, at.% is omitted) sample after heat treatment at various temperatures, and it can be seen that equiaxed α phase is observed at 650℃ and 670℃, and that β single phase is observed at 680℃ or higher. Therefore, T in the Mg-18.7 at.% Sc alloy β was defined as 675°C, which is the midpoint between 670°C and 680°C.

[0056] Similarly, in the cases of Mg-19.1Sc-0.5Zn, Mg-17.5Sc-0.5Y, Mg-18.0Sc-0.5Nd, and Mg-17.3Sc-1.0Gd shown in Figs. β The black dots in each figure indicate that the Sc 2 O 3 It was confirmed that the Sc content was 100% and not 100%. 2 O 3 The difference in the amount of is due to differences between the lots of master alloys used, and at present, these amounts are not fully controllable.

[0057] In addition, the concentration of the β phase in the α+β two-phase structure was measured by EPMA. β For example, Fig. 6 shows an example of an optical microscope micrograph of a Mg-Sc-Gd sample in which a β single-phase structure was not obtained even when the heat treatment temperature was increased to 690°C. Since a single-phase structure was not obtained, the alloy composition of this sample is unknown, but the composition of the β phase in the α+β two-phase structure after heat treatment at 690°C is Mg-17.0Sc-0.5Gd, and it is believed that the low stability of the β phase is the reason why a β single-phase structure was not obtained. On the other hand, taking into account the characteristics of the phase diagram, such experimental results can be understood as β This means that T is 690°C.β It is possible to define

[0058] T defined by the above two methods β The results are summarized in Tables 1 and 2. In the tables, the results marked with an asterisk (*) indicate that the T concentration is higher than the β-phase concentration in the two-phase sample. β This is the result of defining

[0059] In addition, T was calculated using multiple regression analysis from all 44 data in Tables 1 and 2. β The regression equation (2) is shown below.

[0060]

number

[0061] In particular, the coefficient of [X] increases by 1 at.% of X. β How many degrees Celsius does it change (ΔT β ) for each element, β The values ​​were -18.3°C for Sc, -17.3°C for Zn, -39.6°C for Y, -44.4°C for Nd, and -46.1°C for Gd, indicating that the β phase was stabilized by the addition of any of the elements.

[0062] Furthermore, the ΔT of each element β ΔT of Sc β By dividing by , the influence of each element on the β phase stability can be evaluated in terms of Sc. For Zn, it is ~1.0 times, for Y, ~2.2 times, for Nd, ~2.4 times, and for Gd, ~2.5 times. Therefore, ΔT β Standard Sc equivalent (Sc eq ) can be expressed as the following regression equation (1).

[0063]

number

[0064] The various Mg alloys shown in Tables 1 and 2 were obtained according to the following methods.

[0065] In order to obtain the alloy compositions shown in Tables 1 and 2, Mg-Sc master alloys (melted by OSTECH Co. Ltd. and Hunan Oriental Scandium Co. Ltd.) with Sc content of about 20-23 at.%, pure Mg (purity >99.9%), and pure X elements (Zn: purity >99.99+%, Y: >99.9%, Nd: >99%, Gd: >99.9%) were melted and cast in a high-frequency melting furnace to produce plate-shaped ingots (thickness 6 mm, length 60 mm, width 20 mm).

[0066] Next, the plate-shaped ingot was hot rolled at 600-650°C to a thickness of approximately 2 mm, and then annealed at 600°C for 24 hours. After that, it was repeatedly cold rolled at a processing rate of 15% and intermediate annealed at 600°C for 15 minutes to obtain a plate-shaped sample (finished as cold rolled) with a final thickness of approximately 1.2 mm. Test pieces were then obtained by performing final heat treatment.

[0067] Specifically, the final heat treatment was performed as follows. First, the plate-shaped sample was cut into a rectangular sample with a length of 50 mm, a width of 5.0 mm, and a thickness of 1.0 mm using a diamond cutter. The rectangular sample was then subjected to a β-phase heat treatment at 600 to 690°C for 30 minutes, and quenched in ice water to obtain a test piece with a crystal grain size of about 50 to 250 μm. In the β-phase heat treatment, the sample was sandwiched between Nb plates with a thickness of about 1 mm to suppress deformation of the sample during heat treatment and quenching.

[0068] (I) Composition analysis The composition of the test piece was analyzed by a field emission electron probe microanalyzer (FE-EPMA) (JEOL, product name JXA-8530F) and confirmed to be the compositions listed in Tables 1 and 2. Specifically, the test piece was mirror-polished and then measured. The composition concentration was determined by averaging 10 points, excluding the maximum and minimum 2 points, after point analysis of 12 points.

[0069] [Table 1]

[0070] [Table 2]

[0071] <Second additional element> Moreover, the Mg alloy according to one embodiment further contains at least one selected from the group consisting of Ca, Mn, Zr, and Ce as a second additive element, and the content of the second additive element is preferably 0.01 at.% or more and 2.0 at.% or less, and the sum of the content of the first additive element and the content of the second additive element is preferably 9 at.% or less. By having the Mg alloy have this configuration, it is possible to obtain an Mg alloy that has both sufficient ductility and strength.

[0072] [Method of manufacturing Mg alloy] One embodiment of the present invention is a method for producing a Mg alloy having a BCC phase and transformation induced plasticity, which comprises a melting step of melting each component (Mg, Sc, and the first additive element) so that the alloy contains Mg as a main component, Sc in the range of more than 10 at.% and not more than 25 at.%, a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at.% to 9 at.% and the balance consisting of Mg and inevitable impurities, a solution treatment step of solutionizing the alloy at a temperature of 500°C or higher, and a cooling treatment step of cooling the alloy at a cooling rate faster than 1000°C / min.

[0073] <Dissolution process> In one embodiment of the manufacturing method, each element is added in a predetermined amount and melted in an inert gas atmosphere. More specifically, each element is added and melted in an inert gas atmosphere so that the Mg alloy contains Mg as the main component, Sc in the range of more than 10 at.% and 25 at.% or less, a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at.% or more and 9 at.% or less, and the balance consists of Mg and inevitable impurities. Here, the method used for melting is preferably high-frequency heating and melting. The melted alloy is made into a molten ingot, and is processed into a predetermined shape by hot rolling and cold rolling to obtain a precursor of the Mg alloy.

[0074] In the melting step, each component (Mg, Sc, the first additive element, and the second additive element) may be melted so that at least one selected from the group consisting of Ca, Mn, Zr, and Ce is further contained as a second additive element, the content of the second additive element is 0.01 at.% or more and 2.0 at.% or less, and the sum of the content of the first additive element and the content of the second additive element is 9 at.% or less. By adding the above-mentioned predetermined amount of the second additive element in the melting step, the ductility and strength of the Mg alloy become more sufficient.

[0075] <Solution process> The solution treatment process is a process in which the Mg alloy precursor obtained in the melting process is solutionized at a temperature of 500°C or higher. In the solution treatment process, the Mg alloy precursor obtained in the melting process is heated to a solution temperature of 500°C or higher, thereby transforming a part of the crystal structure of the Mg alloy precursor into the BCC phase.

[0076] The lower limit of the solution temperature is 500°C or more, but it depends on the composition of the sample, and is preferably 550°C or more, and more preferably 600°C or more. By setting the lower limit of the solution temperature to the above value or more, the components constituting the Mg alloy can be more completely solutionized, and a sufficient BCC phase can be formed, so that TRIP is more likely to occur. In addition, the upper limit of the solution temperature is preferably 800°C or less, and more preferably 750°C or less. By setting the upper limit of the solution temperature to the above value or less, it is possible to prevent the materials constituting the Mg alloy from melting. In general, the temperature can be lowered as the Sc content is increased. In alloys with a relatively high Sc content, complete solution can be achieved at a temperature of about 500°C, but in the case of alloys with a low Sc content, solution must be achieved at a higher temperature.

[0077] The time for treating the Mg alloy precursor at the solution temperature is not particularly limited, but is preferably 1 minute to 24 hours, more preferably 10 minutes to 12 hours, more preferably 15 minutes to 6 hours, and more preferably 20 minutes to 1 hour. By keeping the treatment time within the above range, it is possible to form a sufficient BCC phase while avoiding the influence of oxidation in the Mg alloy.

[0078] In addition, the Mg alloy produced by the production method according to one embodiment may have a BCC phase volume fraction of 100% by volume, as described in the "BCC phase" section. Also, as described in the "BCC phase" section, the BCC phase volume fraction may be less than 90% by volume, and the lower limit of the BCC phase volume fraction is not particularly limited, but may be 50% by volume or more, 60% by volume or more, 70% by volume or more, or 80% by volume or more.

[0079] <Cooling Treatment Step> The cooling treatment step is a step of cooling the precursor of the Mg alloy that has been subjected to the above-mentioned solution treatment step at a cooling rate faster than 1000°C / min. The cooling treatment step can be carried out, for example, by immersing the precursor of the Mg alloy that has been subjected to the above-mentioned solution treatment step in ice water. The precursor of the Mg alloy that has been subjected to the cooling treatment step here may be used as the Mg alloy.

[0080] <Prescription Processing> Moreover, the manufacturing method according to one embodiment preferably includes an aging treatment step of performing aging treatment at a temperature range of 50° C. to 400° C. after the cooling treatment step. By including this step, the strength of the Mg alloy can be improved. In the manufacturing method according to one embodiment, the precursor of the Mg alloy that has been subjected to aging treatment may be used as the Mg alloy.

[0081] [Application] The uses of the Mg alloy according to one embodiment of the present invention and the Mg alloy produced by the production method are not particularly limited, but they can be used, for example, as structural materials (various parts such as parts, casings, and skeletal members) for electronic devices, transport equipment, medical devices, etc. Here, medical devices include various devices such as stents, bone plates, and coils, and among them, stents used in blood vessels require excellent ductility and strength, so the Mg alloy of the present invention can be suitably used.

[0082] Although the embodiments of the present invention have been described in detail, it is apparent that the same are illustrative and exemplary, not restrictive, and the scope of the present invention should be interpreted by the appended claims. EXAMPLES

[0083] The effects of the present invention will be explained using the following examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following manufacturing examples and examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the technical scope of the present invention is not limited only to the following examples. The ratios of the amounts of raw materials used as solutions or dispersions (units: "parts by mass", "% by mass") are all values ​​calculated as solid content. Unless otherwise specified, each operation was performed at room temperature (hereinafter, room temperature is defined as 20°C).

[0084] In order to obtain the alloy compositions of Examples 1 to 12 and Comparative Examples 1 to 7 shown in Table 3, Mg-Sc master alloys (melted by OSTECH Co. Ltd. and Hunan Oriental Scandium Co. Ltd.) containing about 20 to 23 at.% Sc, pure Mg (purity >99.9%), and pure X elements (Zn: purity >99.99+%, Y: >99.9%, Nd: >99%, Gd: >99.9%) were melted and cast in a high-frequency melting furnace to produce plate-shaped ingots (thickness 6 mm, length 60 mm, width about 20 mm).

[0085] Next, the plate-shaped ingot was hot rolled at 600-650°C to a thickness of approximately 2 mm, and then annealed at 600°C for 24 hours. After that, it was repeatedly cold rolled at a processing rate of 15% and intermediate annealed at 600°C for 15 minutes to obtain a plate-shaped sample (finished as cold rolled) with a final thickness of approximately 1.2 mm. Test pieces were then obtained by performing final heat treatment.

[0086] Specifically, the final heat treatment was carried out in the following manner. First, the plate-shaped sample was cut into a rectangular sample with a length of 50 mm, a width of 5 mm, and a thickness of 1.0 mm using a diamond cutter. Then, in order to obtain the β phase, the rectangular sample was subjected to a solution treatment at 500 to 690°C for 30 minutes, and quenched in ice water. During the heat treatment, the sample was sandwiched between Nb plates with a thickness of about 1 mm to suppress deformation of the sample during the heat treatment and quenching.

[0087] As shown in Table 3, the examples are ternary alloys made of Mg-Sc-X, and the comparative examples are binary alloys made of Mg-Sc without X. eq (at.%) was calculated based on the following formula.

[0088]

number

[0089] In addition, the T β was calculated based on the following formula (2) and shown in Table 3.

[0090]

number

[0091] The specific methods for each measurement are described below.

[0092] (I) Composition analysis The composition of the test piece was analyzed by a field emission electron probe microanalyzer (FE-EPMA) (JEOL, product name: JXA-8530F) and it was confirmed that each composition was as shown in Table 3. Specifically, the EPMA analysis was performed by polishing the test piece to a mirror finish and then measuring. The composition concentration was determined by averaging 10 points, excluding the maximum and minimum 2 points, after point analysis of 12 points.

[0093] (II) Particle size calculation The crystal grain size was calculated by the linear intercept method from the optical microstructure. Specifically, the test pieces were mirror-polished, chemically etched, and then observed.

[0094] (III) Tensile test The tensile test was carried out as follows. The test piece was adjusted to a width of 4 mm and a thickness of about 0.5 mm by mechanical polishing, and then the tensile test was carried out. Until the applied strain reached 10%, the cycle of applying N% strain in the Nth cycle and unloading to 0 N (N=1, 2, 3, 4, 5, 6, 7, 8, 9, 10) was repeated, and then the tensile load was applied until the specimen broke. The strain rate was 10 -3 sec -1 The length between the grips (deformation part) was 15 mm. The tensile test was performed using an Autograph AG-X plus (manufactured by Shimadzu Corporation).

[0095] Based on the results of the tensile tests, the fracture elongation (El, fracture strain), yield strength (YS, yield strength), and tensile strength (UTS, (ultimate tensile strength)) were calculated for each of the examples and comparative examples.

[0096] The elongation at break (El) was calculated as the elongation percentage ((length of test piece at break-length of test piece before test) / (length of test piece before test)×100(%)) of the Mg alloy stretched according to the above tensile test conditions until it broke. The yield strength (YS) and tensile strength (UTS) were calculated from the stress-strain curves obtained as a result of the above tensile tests. As examples, the stress-strain curves obtained as a result of the tensile tests of Examples 1, 7, 8 and 12 are shown in Figs. 7 to 10, respectively.

[0097] (IV) Phase composition survey XRD measurements were performed at room temperature to investigate the constituent phases of the test pieces before and after the tensile test (after fracture). For the test pieces before the tensile test, small pieces of about 4 mm wide and 5 mm long were cut from any part of the test piece, and measurements were performed after mirror finishing. For the test pieces after fracture, small pieces of about 4 mm wide and 5 mm long were cut from the vicinity of the fractured part, and measurements were performed after mirror finishing. The test pieces were polished with SiC paper and then mirror finishing with diamond paste. In addition, the X-ray source for the measurements was Cu-Kα radiation, 40 kV, 40 mA. The device used for the XRD measurements was an ULTIMA IV manufactured by Rigaku Corporation.

[0098] <Results and Discussion> The following describes the measurement results for the test pieces after the tensile test, i.e., after the fracture. The surfaces of the test pieces before the tensile test and the test pieces loaded with 10% strain in the tensile test were observed according to the method described above in "(IV) Investigation of the constituent phases." It was confirmed that the volume fraction of the BCC phase was reduced in the test pieces loaded with 10% strain compared to before the test.

[0099] As described above, Figures 7 to 10 show stress-strain curves at room temperature for the test pieces of Examples 1, 7, 8, and 12, which exhibited fracture elongation due to transformation induced plasticity. Figures 7 to 10 all show a full view, and it was found that the test pieces of Examples 1, 7, 8, and 12 exhibited excellent fracture elongation of about 25% to 65% at 0°C to 50°C.

[0100] Furthermore, Table 3 shows the measurement results of fracture elongation (El (Elongation), Fracture Strain), yield strength (YS, Yield Strength), and tensile strength (UTS, (Ultimate Tensile Strength)) for each of the Examples and Comparative Examples. The test pieces of the Examples (Mg-Sc-X alloys) exhibited fracture elongation, yield strength, and tensile strength equivalent to or greater than those of the test pieces of the Comparative Examples (Mg-Sc binary alloys). This shows that the Mg-Sc-X alloys of the Examples are excellent in both ductility and strength at temperatures between 0°C and 50°C.

[0101] Furthermore, similar to the case of the test pieces of the comparative examples (Mg-Sc binary alloys) that have been reported to exhibit transformation induced plasticity, the formation and progression of necking due to applied strain during tensile testing was confirmed in the test pieces of the examples (Mg-Sc-X alloys). The progression of necking can also be seen from the appearance of the test pieces after fracture of Examples 1, 3, 6, 7, 11, and 12 shown in Figure 11.

[0102] 12 to 15 show the results of XRD analysis of the vicinity of the fractured parts of the test pieces of Examples 1 to 12. From these results, it was confirmed that, as in the case of the Mg-Sc binary alloy, the test pieces of the examples also exhibited transformation induced plasticity at 0°C to 50°C. This also means that the test pieces of the examples exhibited good fracture elongation.

[0103] [Table 3]

Claims

1. An alloy mainly composed of Mg, Sc is contained in the range of more than 10 at. % and not more than 25 at. %, A first additive element selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd is contained in an amount of 0.01 at. % or more and 9 at. % or less; The balance is Mg and inevitable impurities. Has a BCC phase, A magnesium alloy that exhibits transformation-induced plasticity in an environment of 0°C to 50°C.

2. The Mg alloy of claim 1 , wherein the volume fraction of the BCC phase decreases when subjected to an applied strain of 10% or more.

3. 2. The Mg alloy according to claim 1, having a breaking elongation of 20% or more and a yield stress of 150 MPa or more and 1000 MPa or less.

4. Sc equivalent (Sc eq 2. The Mg alloy of claim 1, wherein Mg satisfies the following formula (1): [0010] however, 19.0<Sc eq < 21.0 (in at.%), 600<β single phase temperature (T β ) <700 (°C).

5. Further containing at least one selected from the group consisting of Ca, Mn, Zr, and Ce as a second additional element, The content of the second additional element is 0.01 at. % or more and 2.0 at. % or less, 2. The Mg alloy according to claim 1, wherein the sum of the content of the first additional element and the content of the second additional element is 9 at. % or less.

6. The Mg alloy according to any one of claims 1 to 5, wherein the fraction of the BCC phase is less than 90% by volume.

7. A method for producing a Mg alloy having a BCC phase and transformation induced plasticity, comprising the steps of: a melting step of melting each component so that the alloy contains Mg as a main component, Sc in a range of more than 10 at. % and not more than 25 at. %, a first additive element consisting of at least one selected from the group consisting of Li, Al, Zn, Y, Ag, In, Sn, Bi, Nd, and Gd in an amount of 0.01 at. % or more and not more than 9 at. %, and the balance consisting of Mg and inevitable impurities; A solution treatment process at a temperature of 500° C. or higher; A method for producing an Mg alloy, comprising: a cooling treatment step of cooling at a cooling rate of more than 1000°C / min.

8. In the dissolving step, the alloy further contains at least one element selected from the group consisting of Ca, Mn, Zr, and Ce as a second additive element, The content of the second additional element is 0.01 at. % or more and 2.0 at. % or less, 8. The method for producing an Mg alloy according to claim 7, wherein the Mg alloy is melted so that the sum of the content of the first additional element and the content of the second additional element is 9 at. % or less.

9. The method for producing an Mg alloy according to claim 7 or 8, wherein the fraction of the BCC phase is less than 90 volume %.

10. The method for producing an Mg alloy according to claim 7 or 8, comprising an aging treatment step of performing aging treatment in a temperature range of 50°C to 400°C.

Citation Information

Patent Citations

  • Forged article of magnesium alloy and method for forging magnesium alloy

    JP2001040445A

  • Magnesium-lithium alloy, rolled material, molded article, and method for production thereof

    JP2011058089A